Envisioning Workforce Agility Through Embracing A Dynamic Capabilities Model - SHAKHOUR, NOUR (2022)
This empirical research study investigates how dynamic talent management capabilities as a strategic asset contribute to employee agility as a necessary organizational outcome. Through the mediating effects of absorptive capacity and strategic agility as robust dynamic capabilities, under the moderation effect of adaptive organizational culture. The research context is knowledge workers, which has not been a very popular research context in relation to the examined constructs compared to information technology companies, including Small and medium-sized enterprises (SMEs) (Ajgaonkar, Neelam & Wieman, 2022) and manufacturing (Gunasekaran, 1999). The finding is based on a deductive quantitative research design using a positivist approach and a cross-sectional survey collected from knowledge workers holding managerial roles working within the UAE with a sample size of 406 at a 95% confidence interval. The data was analyzed through a covariance-based approach to structural equation modeling (CB-SEM) using IBM SPSS-AMOS version 26. The finding indicates a statistically significant positive relationship between dynamic talent management capabilities and employee agility, both direct and sequential, through the mediating effect of absorptive capacity and strategic agility. Unlike the traditional human resources practices that were widely accepted, it hardly leads to a direct impact on organizational performance.